2011
DOI: 10.1111/j.1530-2415.2011.01267.x
|View full text |Cite
|
Sign up to set email alerts
|

Another View from the Ground: How Laws Like SB1070 and HB2281 Erode the Intergroup Fabric of Our Community

Abstract: In this commentary, we discuss the articles included in ASAP's special issue on Arizona's Senate Bill 1070 and explore the means by which intergroup bias related to the support and implementation of this law may be reduced. Specifically, we briefly discuss the overall conclusions that can be drawn from the articles included in this volume and address questions that still remain regarding the potential effects of this law. Next, we explore potential strategies for reducing bias between Whites and Latinos, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…However, in the current study, this vulnerability appeared for Black, but not for Latino adolescents. One factor that may explain this difference among ethnic‐racial minority groups is that this study took place in Arizona, where anti‐Latino sentiment and bias are woven into public policy (Bean & Stone, ). Research has indicated that institutional policies negatively affect Latino youth in both direct and indirect ways (Santos, Menjívar, & Godfrey, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the current study, this vulnerability appeared for Black, but not for Latino adolescents. One factor that may explain this difference among ethnic‐racial minority groups is that this study took place in Arizona, where anti‐Latino sentiment and bias are woven into public policy (Bean & Stone, ). Research has indicated that institutional policies negatively affect Latino youth in both direct and indirect ways (Santos, Menjívar, & Godfrey, ).…”
Section: Discussionmentioning
confidence: 99%
“…Assumptions that people of color in the United States are foreigners continue to have systemic impacts today, resulting in racial profiling (Epstein & Goff, 2011; Fisher et al, 2011; Nier et al, 2012). Arizona SB 1070 requires police to assess the immigration status of anyone they reasonably believe may be an undocumented immigrant (Delgado, 2018) and makes it illegal for citizens to transport undocumented immigrants—which has resulted in the targeting of people of color (Bean & Stone, 2012). Profiling of this kind is not limited to Arizona.…”
Section: Establishing White Superioritymentioning
confidence: 99%
“…Assumptions that people of color in the U.S. are foreigners continue to have systemic impacts today, resulting in racial profiling (Epstein & Goff, 2011;Fisher et al, 2011;Nier et al, 2012). Arizona SB 1070 requires police to assess the immigration status of anyone they reasonably believe may be an undocumented immigrant (Delgado, 2018) and makes it illegal for citizens to transport undocumented immigrants-which has resulted in the targeting of people of color (Bean & Stone, 2012). Profiling of this kind is not limited to Arizona.…”
mentioning
confidence: 99%